ANALYSIS OF PUBLIC PERSPECTIVE ON NEWS REPORTING ON THE VIOLENCE CASE BETWEEN JOHNNY DEPP AND AMBER HEARD - Tiara Mesias Purbaningrum; Ardiansyah Ardiansyah; Edi Santoso (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2025)
The defamation trial between Johnny Depp and Amber Heard had become a hot topic of conversation in society. The incident highlighted the fact that Amber Heard, who is a woman, had committed an act of violence against Johnny Depp, who is a man. Male victims are often underestimated by society because of gender stereotypes that men are stronger than women. Moreover, the media still perpetuates this stigma with publishing articles that tend to diminish male victims. This study aims to analyze how the media influences people's perspectives regarding the trial and whether there is gender bias among netizens, especially on social media like Twitter, in providing their opinions. This research uses the mixed method, which is a combination of qualitative and quantitative. Quantitative analysis techniques in this study used Social Network Analysis (SNA) and Digital Opinion Movement (DMO) using Netlytic, while qualitative analysis techniques used literature reviews, in which data were sourced from news articles and journals. The results show that the perspectives of some Twitter users are affected by the media, which tends to be biased. However, most of the others, especially Johnny Depp's supporters, were not affected by this news because of their loyalty and fanaticism towards him. Keywords: social network analysis, johnny depp, amber heard, gender bias, violence